Lokalny rynek pracy w Polsce: The local labour market in Poland - Ginter, Michał (Management and Administration Journal, 2021)
The research related to the diversification on the local labour market pointed that professional activity of the society in Poland regardless a slow growth has not approached the level that is to observe in the EU. The diversification occurs especially on the district labour market and is caused by its historical background. The worst situation prevails in the east and northwest Poland. The best situation concerns cities, agglomeration and districts located around the towns. The characteristic feature of the polish economic transformations is gradual growth of the importance of big regional towns with a concurrent privation of the importance of local towns. The research proved the problems with incoming of young people with higher education on the labour market. The mobility of society has grown what means an enhancement of the tendency to look for a job not only in the place of residence but outside as well.